Waikato GP perspectives on obesity management in general practice: a short report - Ross Lawrenson; Lisette Burrows; Fiona Campbell; Lynne Chepulis; Kimberley Norman (CSIRO Publishing, 2022)
Introduction Obesity is a multifaceted clinical and public health issue affecting over 34% of New Zealand adults. The Ministry of Health has positioned general practice as the best-suited location for addressing the health effects of obesity. Previous literature has identified barriers to the delivery of effective obesity management in general practice. Aim To explore Waikato GP perspectives to determine areas for improving the care of adults with weight problems. Methods A short exploratory questionnaire was used to collect data from 29 GPs across the Waikato region. Descriptive statistics and content analysis were used. Results The majority of GPs reported: they would wait for their patient to raise the issue of their weight; would offer weight advice themselves as a first option before considering referral; did not view general practice as best suited in tackling the obesity epidemic; and utilised bariatric surgery as a referral option while noting the inequities in access. Discussion The survey identified barriers to discussing weight with patients and in finding effective treatment options. Psychosocial and sociocultural aspects were recognised as contributing factors to obesity, but not highlighted as available treatment options. Bariatric surgery was reported as a viable option for treatment, but with barriers to access in the public system. This study found strong trends and themes, which identify an urgent need for further exploration into weight management pathways in New Zealand.